1998
DOI: 10.1002/(sici)1097-0258(19980315/15)17:5/7<517::aid-sim799>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Missing quality of life data in cancer clinical trials: serious problems and challenges

Abstract: Measurement of quality of life (QOL) in cancer clinical trials has increased in recent years as more groups realize the importance of such endpoints. A key problem has been missing data. Some QOL data may unavoidably be missing, as for example when patients are too ill to complete forms. Other important sources are potentially avoidable and can broadly be divided into three categories: (i) methodological factors; (ii) logistic and administrative factors; (iii) patient-related factors. Logistic and administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
111
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 189 publications
(113 citation statements)
references
References 0 publications
1
111
0
1
Order By: Relevance
“…In most studies in which both survival and QOL is determined, the latter is a secondary endpoint. Experienced clinicians and data managers in collecting primary endpoints of survival, tumor response, and toxicity, may view QOL as a subsidiary outcome measure [1]. Both the power analysis for determining sample size and other considerations have been based on the survival endpoint.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…In most studies in which both survival and QOL is determined, the latter is a secondary endpoint. Experienced clinicians and data managers in collecting primary endpoints of survival, tumor response, and toxicity, may view QOL as a subsidiary outcome measure [1]. Both the power analysis for determining sample size and other considerations have been based on the survival endpoint.…”
mentioning
confidence: 99%
“…The international workshop for "Missing Data in Quality of Life Research in Cancer Clinical Trials: Practical and Methodological Issues" reported that trials are often designed with the QOL interval of 3 weeks while on treatment and annually for 5 years [1]. But the design problem for the QOL assessment interval in clinical trials is illustrated by examples from a retrospective review of studies over the last 10 years in which permission to use the Lung Cancer Symptom Scale (LCSS) was requested.…”
mentioning
confidence: 99%
See 3 more Smart Citations